Virtual University As a Horizon of Higher Education Modernization - Beilin, M.V.; Soina, I.Yu.; Dyachenko, Y.A.; Semenova, Yu.A. (KnE Social Sciences, 2021)
The research aim is to analyze the ontological foundations of virtual education in an information society. Among the methods of research used are analysis, synthesis, abstraction, comparison, interpretation, systematization, classification, conceptualization, structural, functional and prognostic methods. The Virtual University is considered as a networking institution that creates unique opportunities for both spontaneous and purposeful manipulation of human development. It is argued that a virtual university must be built with new values in mind: openness, accessibility, democracy, non-discrimination for people with disabilities and other needs of the individual and society. It is argued that the formation of a new picture of the world, which assumes the responsibility of mankind to himself \herself and to nature, the increase of the value of human life, freedom of choice, is also the reason for the formation of new axiological markers that define the virtual university as an information society phenomenon. The research has fixed that the presence of a virtual knowledge environment, in which the learning process unfolds, gives rise to the need to develop a virtual culture, which is a special form of communication between the education subjects in the process of knowledge production and consumption. Virtual communication is defined as a subspecies of semantic communication, which involves the exchange of both information and knowledge. An information society based on the world information economy (knowledge economy) stimulates the development of a planetary information infrastructure that defines the educational trends of the 21st century. In the information society, economic activity is ensured by the information and communication environment, an integral part of which is education. Along with the virtual economy, the virtual financial system, etc., there are virtual educational phenomena, including a virtual university. Keywords: virtual university, educational space, global informatics, post-material values, innovation